PENGARUH KOMPETENSI DAN KOMITMEN ORGANISASIONAL SERTA KOMPENSASI TERHADAP KEPUASAN KERJA DAN KINERJA DOSEN PERGURUAN TINGGI KESEHATAN SWASTA DI KOTA SAMARINDA - ANDIK SUPRIYATNO; PROF. DR. H. DJOKO SETYADI, M.SC; FELISITAS DEFUNG, SE,MA.Ph.D (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2019)
ABSTRACTThe Influence of Competence and Organizational Commitment and Compensation to Job Satisfaction and Performance of Private Higher Education Lecturer in Samarinda City This research is an explanatory research which analyze the influence of exogenous variables of competence, organizational commitment, and compensation to endogenous variable of job satisfaction and performance of private health college lecturer in Samarinda city. The analysis was conducted by path analysis using 97 respondents.The results of the analysis show that: Competence has a positive and significant effect on job satisfaction; Competence has positive and insignificant effect on performance; Organizational commitment has positive and insignificant effect on job satisfaction; Organizational commitment has a positive and significant impact on performance; Compensation has positive and significant impact on job satisfaction; Compensation has positive and insignificant effect on performance, and; Job satisfaction has a positive and significant effect on lecturer performance.